1992
DOI: 10.1056/nejm199212313272701
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between Self-Reported and Actual Caloric Intake and Exercise in Obese Subjects

Abstract: The failure of some obese subjects to lose weight while eating a diet they report as low in calories is due to an energy intake substantially higher than reported and an overestimation of physical activity, not to an abnormality in thermogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
573
9
15

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,134 publications
(633 citation statements)
references
References 26 publications
32
573
9
15
Order By: Relevance
“…First, both occupational and domestic activity data rely on selfreport, which can lead to recall bias. Studies have shown that overweight individuals tend to over-report their physical activity (Lichtman et al, 1992;Buchowski et al, 1999); however, the majority of this work has not been done in populations from lower-income developing countries where the stigma with being overweight is much less established. Nonetheless, if this were the case in these data, overreporting of activity data would only serve to attenuate the estimates by misclassifying overweight individuals as being more active than they truly are.…”
Section: Discussionmentioning
confidence: 99%
“…First, both occupational and domestic activity data rely on selfreport, which can lead to recall bias. Studies have shown that overweight individuals tend to over-report their physical activity (Lichtman et al, 1992;Buchowski et al, 1999); however, the majority of this work has not been done in populations from lower-income developing countries where the stigma with being overweight is much less established. Nonetheless, if this were the case in these data, overreporting of activity data would only serve to attenuate the estimates by misclassifying overweight individuals as being more active than they truly are.…”
Section: Discussionmentioning
confidence: 99%
“…The problem has been identi®ed by several external markers of intake: ®rst, comparisons between self-reported energy intake and the energy intake required to maintain body weight in longterm metabolic studies (Lichtman et al, 1992;Mertz et al, 1991); second, comparisons between reported nitrogena protein intake and 24-h urinary nitrogen excretion where the 24-h urine collection has been validated by the PABA-CHEK technique (Bingham & Cummings, 1983;Bingham et al, 1995;Bingham & Cummings, 1985;Isaksson, 1980); third, comparisons between reported energy intake (EI) and energy expenditure measured by the doubly labelled water technique (EE) (Bandini et al, 1987;Black et al, 1993;Livingstone et al, 1992;Prentice et al, 1986a;Westerterp et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Findings thus far have shown overweight and higher physical activity to be associated with greater under-reporting of energy intake (Lichtman et al, 1992;Prentice et al, 1986;Lansky & Brownell, 1982;Edwards et al, 1993). One investigator (Lichtman et al, 1992) recently noted that`the mechanisms responsible [for the consistent under-report] are not well understood'.…”
Section: Introductionmentioning
confidence: 99%
“…The ®rst domain would be based on physiological characteristics, such as age and body composition as previously reported in the literature. These variables would be used to control for previously reported factors that were associated with underreporting (Lichtman et al, 1992;Bandini et al, 1990;Prentice et al, 1986;Lansky & Brownell, 1982;Pannemans & Westerterp, 1993). The second domain of factors would be psychological indicators that are directly related to concerns about diet and body weight (Wear & Pratz 1987;Gross et al, 1986;Welch et al, 1990;Ruderman 1986;Klesges et al, 1991).…”
Section: Introductionmentioning
confidence: 99%